Preparation and characteristics of ultrafilatration membrane for protein separation - Dung, Tran Thi; Thu Ha, Pham Thi; Thu Phuong, Dinh Thi; Chi, Hoang Thi (Vietnam Journal of Chemistry, 2012)
Ultrafiltration membranes for separation of protein were prepared by immersing phase inversion method. Influence of preparation conditions on separation performance and characteristics of membranes has been investigated in terms of polymer concentration, solvent evaporation time and an additive amount in casting solution. The experimental results show that membranes prepared at a suitable condition could have a good possibility for separation of protein. And, separation capacity as well as characteristics of the formed membranes highly depends on the formation parameters, especially a casting solution composition.